PENGARUH LITERASI KEUANGAN, PAPARAN MEDIA SOSIAL DAN GAYA HIDUP TERHADAP MANAJEMEN KEUANGAN DENGAN TEMAN SEBAYA SEBAGAI VARIABEL MODERASI PADA MAHASISWA KOS DI KOTA BANGKALAN - Urwe Rufaida; Aulia Dawam (STKIP Pesisir Selatan, 2026)
This study aims to analyze financial literacy, social media exposure, and lifestyle on financial management with peers as moderating variables in boarding students in Bangkalan city. The X variables in this study are financial literacy, social media exposure, and lifestyle while the Y variable in this study is financial management and the moderating variable in this study is peers. This research method uses quantitative. The population of this study is all students in Bangkalan city with a sample of 100 respondents determined using the Slovin formula and purposive sampling technique, data collection through observation and distribution of online questionnaires (Google form). Data Analysis Techniques Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA) with the help of IBM SPSS statistics version 27. The results of the study indicate that financial literacy does not have a significant effect on student financial management. Social media exposure has a positive and significant effect on financial management, while lifestyle has a negative and significant effect on student financial management. Peers have no significant effect on financial management. The results of the moderation test show that peers are not able to moderate the influence of financial literacy on variable Y, but are able to weaken the influence on variable X2, and strengthen the influence of variable X3 on financial management.